Factors influencing hibah practice: a scoping review - Bolkan, Nurul Yafisa Sahera; Md Ramli, Raudha; Tumiran, Mohd Amzari; Mustapha, Ramlan (Universiti Teknologi Mara Cawangan Pulau Pinang, 2023)
Hibah is a tool used by Muslims to manage their wealth distribution. Statistics in 2006 showed the number of frozen assets was recorded at RM38 billion. The number of frozen assets has reached RM90 billion in 2022. To reduce this problem, researchers agreed and recommended that Muslims in Malaysia should plan their wealth through hibah. However, hibah practice among Muslims in Malaysia is still low. Thus, this study aims to identify factors that influence the practice of hibah among Muslims in Sabah. This study adopted a scoping review analysis underpinned by the Arksey and O’Malley five-stage framework to categorise the factors that influence hibah practice. The findings show that knowledge, religiosity, and self-efficacy significantly influence hibah practice among Muslim communities. Using hibah as estate planning is the best alternative for the Muslim community. This study suggests a conceptual framework of hibah practice to prove the proposed hypothesis for Muslim communities in Sabah.